The Analysis Of Strategies To Increase The Competitiveness Of Siswandi Rice Production In Pesawaran Lampung District - Bima Andika; Muhamad Emil Rachman (Cita konsultindo, 2024)
The purpose of this research is to determine the strategies that can be used by the Siswandi Rice Factory in facing market competition. The problem faced in business activities is the decreasing level of rice productivity due to the decreasing supply of raw materials caused by weather factors or prolonged drought. In this research, the analysis method used is SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) with the owner of Siswandi Rice Factory as the resource person. The results of research using SWOT analysis identified that Siswandi Rice Factory is in quadrant 1 (Growth Oriented Strategy), which is a very profitable situation. The IFAS result in this study was 3.34, which shows that the Siswandi Rice Factory can utilize its strengths and control its weaknesses. And the EFAS result in this research was 3.39, which shows that the Siswandi Rice Factory can maximize opportunities and minimize threats.And this research also produced 11 alternative strategies that could be used by the Siswandi Rice Factory to increase the company's competitiveness.